Evidence for geometrical barriers in an untwinned YBa2Cu3O7-delta single crystal - Pissas, M.; Stamopoulos, D. (PHYSICAL REVIEW B, 2001)
The local ac and dc magnetic response in an untwinned YBa2Cu3O7-delta crystal has been measured using a microscopic Hall sensor. Due to the low pinning energy at elevated temperatures (near T-c), the ac response of the platelet-shaped crystal is governed by the geometrical barrier. From the field where the first vortex penetrates into the center of the crystal we estimated the first critical field (H-c1). The temperature variation of H-c1 near T-c is compatible with a strongly type-H superconductor, where the fluctuations in the order parameter (Psi) are those of an uncharged superfluid of the three dimensional XY model. In order to extract a reasonable value for the London penetration length at T=0 K, a value c(0)=3 is needed for the core contribution of the line energy of the vortex.